Amores humanos, amores divinos. La Vita Christi de sor Isabel de Villena. - OCAÑA, ANTONIO CORTIJO (Scripta)
The Vita Christi by Sor Isabel de Villena is a paramount text written in medieval Iberia. Based on the Vita Christi by Ludolf of Saxony (the Carthusian), the work can be interpreted as a Vita Mariae for it pays particular attention to the role of the Virgin in Christ's life. This article explores the parallels between Sor Isabel de Villena's hagiographical text and the mythological prose works by Joan Roís de Corella. Both share an interest on love and on describing affects and the emotional inner world of the characters.